Vibrating Profile in the Aerodynamic Tunnel – Identification of the Start of Flutter - Kozanek, Jan; Vlcek, Vaclav; Zolotarev, Igor (Journal of Applied Nonlinear Dynamics, 2026)
The experimental results for the vibrating NACA0015 profile elastically supported in a translation and rotation for a set of increasing Mach numbers of the airflow are presented. The profile was placed in the aerodynamic tunnel of the Institute of Thermomechanics ASCR. The support properties of the profile were modified by three additional masses to control the eigenfrequencies corresponding to transversal vibrations and verified by the identification of the complex eigenvalues (eigenfrequencies, damping) for zero flow velocity in laboratory. The transversal free vibrations as the time functions are graphically depicted for stable vibrations and in the cases of the starting flutter. The start of the flutter was determined from free vibrations of kinematically excited profile. The complex eigenvalues were identified as the functions of Mach number including corresponding limits of the system aeroelastic stability.